Investigating Mediumship/Possession-Relevant Experiences: Contributions from a Feature-Based, Subject-Dependent Approach to Definition and Measurement. - Maraldi, Everton De Oliveira; Fischer, Ronald; Varejão, Maria Vitoria De Lima; Bortolini, Giovanna Novaes; Bêta, Maria Clara Laport; Hartle, Larissa; Bortolini, Tiago; Moll, Jorge (Transcultural Psychiatry, 2026)
Non-ordinary experiences such as hearing voices, losing control over one's body or mediumship/possession, are observed across cultures. However, there is a notable lack of instruments specifically designed to measure these experiences from a subject-centered, culturally sensitive perspective, with existing measures offering limited coverage ofexperiences that may be particularly salient for religious groups cultivating mediumship/possession practices. This study proposes a novel, feature-based, subject-dependent approach to defining and measuring relevant mediumship/possession-like experiences, grounded in cross-culturally recognizable phenomenological features while respecting participants' culturally specific interpretations. Using Brazil as a case study, given its rich mediumship traditions, we developed and validated a new set of items that capture relevant experiences within mediumship/possession through a multi-step process informed by the Inventory of Non-Ordinary Experiences. Study 1 involved a systematic review of dissociation and mediumship research in Brazil to create an item pool. Study 2 refined these items with input from mediumship practitioners and religious leaders. Study 3 validated the items in a Brazilian population sample, and Study 4 estimated the prevalence of these experiences in a representative sample. The study validated 10 key features of mediumship/possession-relevant experiences and found high prevalence rates in Brazil, with some experiences reported by more than 60% of participants. Our findings highlight the importance of feature-based, culturally informed approaches to studying mediumship/possession and offer recommendations for future research into their phenomenology, prevalence, and cultural appraisals.